2020
DOI: 10.1038/s41467-020-17997-6
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing intracellular accumulation and target engagement of PROTACs with reversible covalent chemistry

Abstract: Current efforts in the proteolysis targeting chimera (PROTAC) field mostly focus on choosing an appropriate E3 ligase for the target protein, improving the binding affinities towards the target protein and the E3 ligase, and optimizing the PROTAC linker. However, due to the large molecular weights of PROTACs, their cellular uptake remains an issue. Through comparing how different warhead chemistry, reversible noncovalent (RNC), reversible covalent (RC), and irreversible covalent (IRC) binders, affects the degr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
148
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(153 citation statements)
references
References 58 publications
5
148
0
Order By: Relevance
“…Similarly, Gray et al reported an example of non-cooperative binding between BRD4-dBET23-CRBN, which generated potent degraders (Nowak et al, 2018). To understand this apparent discrepancy, the formulated hypothesis is that the ternary complex formation not only depends on binding affinity rates and positive cooperativity but also on the absolute concentration of the target and the E3 ligase in cells (Guo et al, 2020). Therefore, quantitative western blots to measure their intracellular levels should be done in parallel to kinetic studies.…”
Section: Ternary Complex Formation and Cooperativitymentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, Gray et al reported an example of non-cooperative binding between BRD4-dBET23-CRBN, which generated potent degraders (Nowak et al, 2018). To understand this apparent discrepancy, the formulated hypothesis is that the ternary complex formation not only depends on binding affinity rates and positive cooperativity but also on the absolute concentration of the target and the E3 ligase in cells (Guo et al, 2020). Therefore, quantitative western blots to measure their intracellular levels should be done in parallel to kinetic studies.…”
Section: Ternary Complex Formation and Cooperativitymentioning
confidence: 99%
“…In particular, Xue et al generated covalent irreversible BTK degraders that, in contrast to the previous findings (Tinworth et al, 2019), achieved excellent degradation potency in cells (Xue et al, 2020). Moreover, Guo et al sought to measure the efficacy of BTK PROTACs by comparing different warhead chemistry: reversible non-covalent (RNC), reversible covalent (RC), and irreversible covalent (IRC) (Guo et al, 2020). In parallel, another extended work conducted by London's group has been pursued with the same purpose (Ronen et al, 2020).…”
Section: Covalent Vs Non-covalent Protacsmentioning
confidence: 99%
See 2 more Smart Citations
“…PROTACs bearing RC POI ligands have been described for BTK targeting PROTACs. 99,100 Interestingly, the RC BTK PROTACs are not as efficacious as covalent PROTACs, despite the fact that RC PROTACs should retain their catalytic nature since the PROTAC can dissociate. This suggests that ubiquitination and degradation may be on a faster time scale than dissociation, or may even impede dissociation.…”
Section: Reversible-covalent E3res -Keap1mentioning
confidence: 99%